Value relevance of accounting figures in presence of earnings management. Are enforcement and ownership diffusion really enough? - Callao, Susana; Cimini, Riccardo; Jarne, José Ignacio (Journal of Business Economics and Management, 2016)
The study assesses and compares the value relevance (VR) of accounting numbers in entities that experienced high discretionary accruals intensity and so possible earnings management (EM) behaviours, testing whether and in what extent the quality of enforcement and governance mechanisms act as moderating factors on the relation EM-VR. Based on a sample of 2 667 European non-financial entities, the results show that while the VR of earnings is low in entities that experienced high discretionary accruals intensity, book value increases its VR. The study also shows that the quality of enforcement mechanisms and the ownership diffusion (that proxies the quality of corporate governance) are effectively able to obstruct the loss of VR of earnings. The value added of the paper consists in showing that both the quality of enforcement and the ownership diffusion contrast only in part and in different manner the loss of VR of earnings, due to the presence of EM behaviours, acting only in part as moderating factors.